Wettability and printability of SAC305-xTiO2 Pb-free solder paste on Cu substrate - Sukpimai, K.; Suwannakrue, W.; Kanlayasiri, K. (My University, 2019)
This paper was aimed to study on effects of TiO2 nanoparticles on wettability and printability of SAC305-xTiO2 Pb-free solder on Cu substrate. TiO2 nanoparticles at various concentrations (0.00, 0.05, 0.10, 0.50, and 1.00 wt%) were introduced to SAC305 solder paste by mechanical mixing. Wettability of the solder on Cu substrate was measured in terms of contact angle while printability was calculated from the ratio of printed volume on Cu substrate to ideal volume of solder on the substrate. Results showed that the introduction of TiO2 nanoparticles decreases the contact angle and 0.33 wt% TiO2 is the optimal concentration providing the lowest contact angle within the experimental range. Moreover, the addition of TiO2 nanoparticles reduced the printability of solder paste on Cu substrate. The higher amount of nanoparticles gave the lower printability. Simultaneous optimization on wettability and printability was also performed to find the optimal TiO2 concentration.